Assessment of Driving Automation Interfaces via Visual Attention Measures: A Literature Review. (September 2021) - Kanaan, Dina; Powell, Mattea; Donmez, Birsen
Different in-vehicle interface designs have been proposed to support drivers in operating vehicle automation systems. Measures of visual attention are particularly useful in the evaluation of such interfaces, especially in conditions when driving performance measures cannot be used, i.e., when the driver is not physically controlling the vehicle. In this paper, we present a literature review on visual attention measures in the assessment of in-vehicle interfaces to support the use of driving automation. This review was a preliminary pilot study for a larger, ongoing scoping review investigating visual attention and driving automation more broadly. Based on a systematic search of one engineering literature database, this review focused on driving automation that does not require the driver to physically control the vehicle but does require driver involvement in some capacity. The findings of this review contributed to the development of the larger review and can help identify future research trends.